Contextual and subjective indices of coping strategies in breast cancer screening: A longitudinal investigation. - Savoie, Jo Anne. (University of Ottawa (Canada), 1999)
With the aim of better understanding the concept of coping, the objectives of the study were to (1) examine the concordance of subjective and contextual coping indices, (2) investigate changes in the use of coping strategies as a natural stressor unfolds, and (3) predict levels of psychological stress from coping strategies used when faced with a health threat. A sample of 828 women undergoing routine breast screening completed subjective measures of stress and coping at four time points (prior to the screen as well as 24 hours, 20 days and three months follow-up). Contextual coping was gathered at the three-month follow-up for all participants with a false positive screen along with matched negative-screen counterparts (n = 132). Correlational analyses revealed poor concordance between the subjective and contextual indices of coping, with a trend toward overreporting approach and underreporting avoidance strategies compared to experimenter ratings of coping. The use of contextual avoidance and approach strategies over time peaked following the result of the screen for the positive screen group, yet remained relatively stable across time for those with the negative screen group. A stage effect was noted on subjective strategies, with all participants reporting higher levels of approach coping from pre-screen to post-result. At post-result, group differences showed that women with a positive screen displayed, but did not report on the subjective measure, more behavioral and cognitive avoidance strategies than the negative screen group. No differences between groups were noted at follow-up on either coping measure. In the prediction of stress, prospective levels of subjective cognitive avoidance predicted higher levels of stress after notification of the result. The use of contextual strategies was not found to be a significant predictor. The strengths and limitations of the study are presented in the discussion along with the research and clinical implications.
Keywords: Psychology, Clinical.